Work readiness of pharmacy graduates: An exploratory study. - Wei Jin Wong; Ronald F.S. Lee; Li Yun Chong; Shaun Wen Huey Lee; Wee Ming Lau (Elsevier, 2024)
Introduction: The recent global pandemic of Covid-19 caused various disruptions. Among them were face-to-face teaching and learning activities being switched to virtual sessions in accordance with health authorities recommendations. The impact of these changes on work readiness of pharmacy graduates is unknown. Aim: This study aims to determine the impact of pharmacy graduate's work readiness, particularly those that had their studies disrupted from the pandemic. Methods: Practicing pharmacists with supervisory experience were interviewed on their opinions on work readiness of early career and intern pharmacists. Specifically, they were asked to comment on work readiness of pharmacy graduates who had their later stage of pharmacy education impacted by the pandemic. Data was transcribed verbatim and thematically analysed. This was also supplemented with quantitative data from graduating students in 2020 and 2021 using the Work Readiness Scale. Results: Qualitative feedback showed four themes related to workforce readiness: work competence, social intelligence, personal characteristics, and organizational acumen. Preceptors interviewed noted differences in communication abilities when interacting with patients. However, this improved with time. Quantitative data collected from graduates via the validated Work-Readiness Scale also showed a more positive agreement towards perceived work readiness. These graduates were comfortable with using technology as they had used these extensively in their learning during the pandemic and thus was comfortable in adopting digital health tools in their practice. Conclusion: Although graduates reported to be work ready, there were gaps in communication skills and confidence levels when interacting with patients, as reported by supervising preceptors. Graduates also described this sense of 'missing out' from not having the opportunity to attend face-to-face activities like their originally planned hospital placements and how it impacted their choice of career. As pharmacists continue to play vital roles as members of the broader healthcare workforce, both in clinical and nonclinical settings, learnings from this study should be considered in designing educational activities to train and develop the workforce of the future.